Kajian Terhadap Migrasi Plastik Hasil Induksi Panas pada Beberapa pH dan Jenis Asam Organik - Haseama, Gabriella Mutiara; Wijaya, I M. Mahaputra; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): September, 2020)
In Indonesian street food vendor, most of hot acidic food and drinks are served with plastic packaging and plastic cutlery. This research is aimed to study about the presence of plastic’s component migration as a result of heat induction in the presence of various pHs and organic acid, and to identify the types of migrated plastic components through its functional groups. In this research, the samples were 10 plastic packaging and cutlery made from LDPE, HDPE, PP, PE, and PS plastic. Acetic acid, citric acid, and lactic acid and three levels of pH which were pH 4, 5, and 6. Temperatures of 80 and 100 ? were used as representation of food and drinks served warm. Each samples were conditioned in each organic acids solutions with different pH (pH 4, 5, and 6) and thermal treatments were carried out for 1 hour in each temperature. The plastic migrations were detected using UV-Visible spectroscopy, followed by FTIR spectroscopy to identify functional groups of the migrated plastic components, followed by prediction of the migrated compound. The results suggested that plastic component migration were detected in all samples, and using lactic acid pH 4, 5, and 6 an antistatic diethanolamides was ruled plausible released from white plastic glass sample. Keywords : plastic migration , organic acids , pH , spectroscopy , temperature .